Hallmarks of nursing students exhibiting unsafe clinical practices: a qualitative study - Akram Ghahramanian; Mostafa Ghasempour; Vahid Zamanzadeh; Leila Valizadeh; Laura A. Killam; Majid Purabdollah; Mohammad Asghari-Jafarabadi (BMC Nursing)
Abstract Background Maintaining and promoting patient safety is a shared responsibility among all participants in the health care system. Educators are required to balance patients’ rights to receive safe care and create a suitable and safe environment for nursing students to learn. Therefore, early identification of students with unsafe clinical practice and intervention may be important measures for improving patient safety. Therefore, the present study was conducted with the aim of identifying the main hallmarks of nursing students with unsafe clinical practice. Methods This qualitative study was conducted with 19 faculty members, nursing students, and supervisors of medical centers. Data collection was performed through purposive sampling and semi structured interviews. Data analysis was performed via conventional qualitative content analysis via MAXQDA10 software. Results The results of the study led to the identification of 2 main categories, “Underdeveloped knowledge and cognitive capacity” and “Underdeveloped personal-professional capacity”, and 6 and 4 subcategories, respectively, as the main hallmarks for identifying students with unsafe clinical practice. Conclusion The findings of this qualitative study expand our understanding of the hallmarks of nursing students with unsafe clinical practice. Undergraduate nursing students with unsafe clinical practice may not have acquired sufficient development and progress in terms of knowledge, skills, and personal-professional characteristics or may not be able to demonstrate them in their practices. Nursing schools must ensure that students have the necessary knowledge, skills, competencies, and personal-professional characteristics to participate in clinical training programs. It is recommended that students with unsafe clinical practices be identified early so that patient safety is maintained and that students are supported in order to correct their weaknesses and improve.